The Typological Peculiarities of the Negative Adverbs of the German Language - Shachilvyan, Naira (Bulletin of Yerevan University B: Philology, 2022)
In this article the typological peculiarities of the negative adverbs of modern German are presented in comparison with the corresponding facts of theArmenian language, which acts here as an etalon language. Negative adverbs are lexicogrammatical means of expressing negation, which are remarkable because their presence inthe composition of a sentence contributes to the manifestation of peculiar features of the formation of negative sentences in different languages, as well as at different stages of the development of one language. It is shown that by the abovementioned means of expressing negation the mononegative type of the modern German language is opposed to the polynegativetype of the Armenian language. The mononegative system of the German language is usuallyexplained by the general tendency towards the maximum possible combination of grammatical structures in this language. In German negative adverbs may function in a sentence asadverbial modifier of time, place and manner and give a negative meaning to the affirmativeform of the predicate and at the same time to the whole statement, performing the function ofgeneral negation, while the equivalent means in the Armenian language are used with thesame function, as a rule, with negative forms of the verb and act as a complex whole. In Armenian negative adverbs are the main negative elements in a sentence, since their presencenecessitates the use of negative forms of the verb, while the opposite fact is not typical here.
Keywords: typological peculiarities; negative adverb; lexico-grammatical means; polynegative language; mononegative language; double negation; negative sentence; general negation; syntactical function; adverbial; semantic field